(untitled) (Mwanga wa Lugha, 2019)
Kenya is a multilingual nation with about eighty different ethnic languages. Kenyan politicians use language as a weapon with which they woo the electorate. One way of so doing is by code switching or code mixing. This paper shows instances of code switching/code mixing while explaining why the Kenyan politicians do so as they address the electorate. In this paper, the concepts of code switching and code mixing are interchangeably used given the varied morpho-syntactic nature of all the languages in use in Kenya. Data for the paper was obtained from the University of Nairobi students who were Communication major and Sociolinguistics major. The discussions in the paper are anchores on selected tenets of Communication Accommodation Theory as espoused by Howard Giles. The paper demonstrates that Kenyan politicians code switch because of the need to be accepted by those from a particular ethnic group they are addressing at that particular time not that they are deficient in the matrix language.